Performance of Earth Troposphere Calibration Measurements With the Advanced Water Vapor Radiometer for the Juno Gravity Science Investigation. Issue 12 (21st December 2021) - Buccino, D. R.; Kahan, D. S.; Parisi, M.; Paik, M.; Barbinis, E.; Yang, O.; Park, R. S.; Tanner, A.; Bryant, S.; Jongeling, A.
Abstract: The performance of an atmospheric water vapor radio path delay measurement and correction is reported using observations of the Juno Spacecraft during gravity field mapping of Jupiter. The Juno Gravity Science instrument measures the Doppler shift on the radio signals between the Juno spacecraft and the Earth‐based observing stations of NASA's Deep Space Network (DSN) during times of closest approach to Jupiter in order to map Jupiter's gravity field. These Doppler measurements are affected by noise sources between the spacecraft and DSN which include charged particles plasma and Earth's troposphere. A pair of redundant Advanced Water Vapor Radiometers (AWVR) co‐located at the DSN's DSS‐25 antenna in Goldstone, CA measure the brightness temperatures at the 22.2, 23.8 and 31.4 GHz spectral lines for water vapor content in Earth's atmosphere. The measurements of water vapor content are reduced into a measurement of radio path delay, which provides high‐precision calibrations of tropospheric noise on the radio links. Analyses of AWVR measurements show that spacecraft tracking errors, after removing other measurable errors from charged particles, are reduced by 46% on average and by as much as 70%, depending on local weather conditions near the Goldstone site. Plain Language Summary: The Juno Gravity Science instrument relies on precise measurements of the Doppler shift of the telecommunications radio link signal between the Juno Spacecraft and the Earth‐based Deep Space Network (DSN) antennas. A radiometer system called the Advanced Water Vapor Radiometer (AWVR) is deployed at the DSN's DSS‐25 antenna in Goldstone, California, to measure the tropospheric path delay seen by radio signals received from deep space. The AWVR calibrates the deep‐space Doppler frequency measurements. Troposphere path delay measurements throughout the Juno prime mission are presented and the measurements are shown to improve the Doppler frequency measurements by 46% on average and by as much as 70%, depending on local weather conditions. Key Points: This research presents the impacts of Earth troposphere path delay on Juno Gravity Science Doppler frequency measurements The Advanced Water Vapor Radiometer (AWVR) measured short‐term and seasonal variations in troposphere path delay in Goldstone, California The AWVR improved Doppler frequency measurements by 46% on average and up to 70% in optimal conditions